Dependence of core-level photoemission spectra on overlayer growth mode: Al on InP(110) - MC GOVERN, IGNATIUS (My University, 1988)
The adsorption of Al overlayers on the clean, cleaved InP(110) surface has been studied, with the InP substrates at room and low (120 K) temperatures, using synchrotron radiation excited soft-x-ray photoemission spectroscopy. This interface exhibits a well-documented exchange reaction at room temperature, and a visual comparison of the spectra taken at 300 and 120 K suggests that this reaction is inhibited at 120 K. However, there are also significant changes in the interface growth mode as the temperature is lowered. The reacted indium feature exhibits a coverage-dependent binding energy, so that its spectral weight is obscured by overlap with the bulk indium feature. Moreover, escape-depth considerations invalidate a simple comparison of reactivity at the two temperatures.
PUBLISHED
Keywords: Physics